1944
DOI: 10.1037/h0056112
|View full text |Cite
|
Sign up to set email alerts
|

Factors in massed and distributed practice.

Abstract: In an earlier paper I concluded from an analysis of the data on massing and distribution of practice that there was experimental evidence for a dual division of learning into 'achievement of insight' on the one hand and 'fixation' on the other. I also predicted that if (and as long as) a novel configuration were unstable, massing of repetitions would be more economical than distribution, since if the configuration were once lost the preliminary process of problemsolving must be gone through again. On the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1950
1950
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Some degree of distribution of practice has facilitated the learning of a wide variety of lower-order tasks (7), but the effect on the more complex tasks has not been clearly demonstrated. Studies of mental mazes (2), problem solving (3), and puzzle solving (1) indicate that massed practice is superior to distributed practice, but the intertrial interval used in the distributed condition was never less than 24 hr. Oseas and Underwood (6), using vals, found that distribution tended to facilitate simple concept learning, but the differences were not statistically significant.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Some degree of distribution of practice has facilitated the learning of a wide variety of lower-order tasks (7), but the effect on the more complex tasks has not been clearly demonstrated. Studies of mental mazes (2), problem solving (3), and puzzle solving (1) indicate that massed practice is superior to distributed practice, but the intertrial interval used in the distributed condition was never less than 24 hr. Oseas and Underwood (6), using vals, found that distribution tended to facilitate simple concept learning, but the differences were not statistically significant.…”
mentioning
confidence: 96%
“…The authors wish to express their gratitude to Dr. B. J. Underwood, who assisted with the study 2. Now at Training Research Laboratory, Department of Psychology, University of Illinois.…”
mentioning
confidence: 99%
“…Specifically, at the very beginning of experimental psychology, Ebbinghaus (1985) found that retrieving study material caused savings during relearning of that material and the basic finding that spaced (or distributed) retrieval practice results in better retention than massed practice has been replicated many times since (e.g., Cook, 1944;Ericksen, 1941;Underwood, 1961). It predicts that making a study item the target of a voluntary action will improve understanding and increase retention over a condition in which the study item is seen or heard with no specific response required.…”
Section: Please Scroll Down For Articlementioning
confidence: 97%
“…In a follow-up study Longley (12) used a "Massed-evenly spaced" time pattern (1,2,3,8,15,22,29,36,43) which, when compared with Miller's (15) four time patterns gave the following results:…”
Section: Further Researchmentioning
confidence: 95%
“…This group was called the Additive-Group. 3. Practice for the next group was conducted on a daily basis including Saturday and Sunday.…”
Section: Boston University School Of Education Research Laboratory mentioning
confidence: 99%